The Role of Counselors in Spiritual Counseling to Reduce Bullying Trauma among Students in Islamic Higher Education Institutions - Yandri, Hengki; Juliawati, Dosi (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
This study aims to examine the role of counselors in providing spiritual counseling services to reduce bullying trauma among students in Islamic higher education institutions. The research design employs a quantitative approach using a survey method. The participants are lecturers from the Islamic Education Guidance and Counseling Department at State Islamic Higher Education Institutions. Data collection instruments include a questionnaire measuring lecturers' readiness and understanding in implementing spiritual counseling. The data analysis technique used is descriptive analysis. The findings indicate that the majority of lecturers feel prepared to provide spiritual counseling services, as reflected in their experience, knowledge, and confidence in integrating Islamic values into the counseling process. However, there is a subset of lecturers who are not fully prepared, highlighting the need for ongoing professional training and support. Despite a high interest in spiritual counseling, its implementation in practice, particularly in addressing bullying cases, remains suboptimal. These findings suggest a gap between interest and practice, emphasizing the importance of developing relevant and practical spiritual counseling models. Overall, the results reinforce the argument that Islam-based spiritual counseling, which incorporates values such as patience, sincerity, reliance on God, and self-purification, can be an effective approach to mitigating the psychological impacts of bullying